PENENTUAN BILANGAN PEROKSIDA MINYAK GORENG BEKAS YANG DIJERNIHKAN MENGGUNAKAN KULIT PISANG KEPOK (Musa acuminata Liin) BERDASARKAN LAMA PERENDAMAN - Iin Kurnia Tasry; Mujahidah Basarang; Mardiah Mardiah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2017)
Cooking oil that has been used repeatedly has adverse health effects if consumed. One of the conditions of cooking oil that can be consumed based on SNI is peroxide number is 10 meq. Efforts to improve the quality of cooking oil can be done with clarification using banana kepok (Musa acuminata Liin) which has been dried. Banana peels can lower peroxide numbers because banana peels contain beta-carotene fat-soluble antioxidants and can inhibit oxidation processes. This research is experimental laboratory that aims to know the peroxide number of used fried oil which is clarified using banana kepok skin (Musa acuminata Liin) based on the duration of immersion, using Iodometri method. From the research result, the peroxide value of used cooking oil is 5,83 meq and after soaked banana peel skin for 1 hour peroxide number is 5.08 meq, soaking 2 hours is 4.10 meq, soaking 3 hours is 3,26 meq, and Soaking 4 hours is 2.8 meq. From the research results can be concluded that the longer immersion peroxide numbers decreased.